2007
DOI: 10.1086/513607
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent 10q22-q23 Deletions: A Genomic Disorder on 10q Associated with Cognitive and Behavioral Abnormalities

Abstract: Low-copy repeats (LCRs) are genomic features that affect chromosome stability and can produce disease-associated rearrangements. We describe members of three families with deletions in 10q22.3-q23.31, a region harboring a complex set of LCRs, and demonstrate that rearrangements in this region are associated with behavioral and neurodevelopmental abnormalities, including cognitive impairment, autism, hyperactivity, and possibly psychiatric disease. Fine mapping of the deletions in members of all three families … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(83 citation statements)
references
References 37 publications
4
77
2
Order By: Relevance
“…clinical genetics | development | ErbB4 | neuregulin | NRG1 R ecurrent microdeletions of chromosome 10q22-q23 that involve the Neuregulin 3 (NRG3) gene have been associated with a heterogeneous group of neurodevelopmental disorders, including developmental delay, cognitive impairment, and autism (1). The chromosome 10q22-q23 locus also shows linkage to schizophrenia in Ashkenazi Jewish and Han Chinese populations (2,3), and noncoding genetic variation in NRG3 has been identified as a putative risk factor for schizophrenia and related neuropsychiatric disorders (4)(5)(6)(7).…”
mentioning
confidence: 99%
“…clinical genetics | development | ErbB4 | neuregulin | NRG1 R ecurrent microdeletions of chromosome 10q22-q23 that involve the Neuregulin 3 (NRG3) gene have been associated with a heterogeneous group of neurodevelopmental disorders, including developmental delay, cognitive impairment, and autism (1). The chromosome 10q22-q23 locus also shows linkage to schizophrenia in Ashkenazi Jewish and Han Chinese populations (2,3), and noncoding genetic variation in NRG3 has been identified as a putative risk factor for schizophrenia and related neuropsychiatric disorders (4)(5)(6)(7).…”
mentioning
confidence: 99%
“…The reciprocal duplications of the Williams-Beuren deletion interval are associated with language delay and autism (Somerville et al, 2005;Van der Aa et al, 2009& Depienne et al, 2007, suggesting that duplications in this genomic region are more closely linked to behavioral deficits that fall within the spectrum of autism disorder. Deletions flanked by segmental duplications are associated with language delay, attention deficit hyperactivity disorder (ADHD), and autism for the 10q22-23 interval (Balciuniene et al, 2007), and a balanced translocation affecting the KCNMA1 gene, which encodes a calcium-activated large conductance potassium channel, on 10q22 has also been reported in a child with autism (Laumonnier et al, 2006). Maternally-derived duplications of the 15q11-13 interval are the most common cytogenetic abnormalities associated with autism (Cook et al, 2001), and maternal as well as paternal-derived deletions are responsible for Angelman and Prader-Willi syndromes, respectively.…”
Section: High-resolution Genetic Datamentioning
confidence: 99%
“…These recurrent aberrations may give rise to new genomic disorders, such as the 15q24 microdeletion syndrome 16 and the 10q22q23 microdeletion syndrome. 23 Targeted microarrays have been developed with target sequences corresponding to genomic regions of known clinical significance, such as the chromosome subtelomeres and regions implicated in well-known human genomic disorders. 24 -27 Using these targeted microarrays, Shaffer et al 28 found clinically relevant genomic alterations in 5.6% of 1500 consecutive cases referred to the clinic for a variety of developmental problems.…”
Section: European Journal Of Human Geneticsmentioning
confidence: 99%